Niger : Selected Issues. (IMF Staff Country Reports; Country Report, 2015)
This Selected Issues paper presents an external stability assessment on Niger. Niger's current account balance deteriorated in 2013, mostly on account of higher food and capital goods imports. The deficit is expected to widen further in 2014-15, mainly driven by large investment in the extractive industry and basic infrastructure. The current account is projected to gradually improve from 2016 as important projects in infrastructure will come to end, the oil and mining sectors come on stream and public and private savings increase. Although aid and foreign direct investments are the main sources of external financing, external borrowing-mainly on concessional terms-has increased significantly.